Rankings universitários em perspectiva : o Ranking Universitário Folha e a construção da excelência - Arthur de Ávila Soares (2022)
In this research, I sought to examine quantification processes and their construction, highlighting the relationship between statistics and politics, based on a case study of the Ranking Universitário Folha, the first and only brazilian university ranking. It is known that each ranking defines its own indicators and weights, evidencing a dispute over what matters in defining the quality of a university. In this sense, the main objective of this research was to explore the Ranking Universitário Folha, seeking to examine and define the idea of university excellence used/elaborated by the ranking and the possible consequences of its use. Methodologically, a comparative document analysis, associated with the quantitative examination, also comparative, of the variables used in the indexes and their weights, based on the review of the international literature on the subject that made it possible to build a classification of the indicators used by the ranking. I found that the concept of university excellence privileges research indicators, especially those on productivity and impact, and, observing the Brazilian case, completely discards (and surprisingly, given the institutional mission of Brazilian universities) the evaluation of extension activities of universities. Furthermore, it was possible to examine the association between this specific political mode of operation of statistics and the construction of indices with the existing discussion in the literature on neoliberal rationality. Rankings, far from being just a metric and neutral numbers, are central pieces in the manufacturing processes of a competitive context among the brazilian universities.